2004
DOI: 10.1111/j.1365-3032.2004.0369.x
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic induction of diapause: opening the black box

Abstract: Abstract. Over several decades, formal experiments measuring diapause responses to variable light inputs have indicated that photoperiodic time measurement in insects is accomplished either by a nonoscillatory 'hourglass-like' mechanism or by oscillatory components of the circadian system. Although both are possible given the present state of our knowledge, a substantial body of evidence strongly suggests that night-length measurement is a function of the circadian system, and that 'hourglass-like' clocks are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 72 publications
(106 reference statements)
1
44
0
1
Order By: Relevance
“…In the present study, one broad trough of diapause inhibition was found with a 1-h light pulse at L9:D15 and L12:D12 in O. furnacalis. These results suggest that photoperiodic time measurement for diapause induction in O. furnacalis resembles an hourglass-like timer (according to Veerman, 2001) or a damped circadian oscillator (according to Saunders et al, 2004). The above-mentioned results suggest that insect species may have developed clock systems with completely different evolutionary origins.…”
Section: Discussionmentioning
confidence: 75%
“…In the present study, one broad trough of diapause inhibition was found with a 1-h light pulse at L9:D15 and L12:D12 in O. furnacalis. These results suggest that photoperiodic time measurement for diapause induction in O. furnacalis resembles an hourglass-like timer (according to Veerman, 2001) or a damped circadian oscillator (according to Saunders et al, 2004). The above-mentioned results suggest that insect species may have developed clock systems with completely different evolutionary origins.…”
Section: Discussionmentioning
confidence: 75%
“…In most cases, light is the primary cue, and the seasonal change in day length is monitored by a so-called "photoperiodic clock" (Bradshaw and Holzapfel 2010). Despite intensive study of the photoperiodic clock for the last 80 years at the phenomenological level, the "black box" approach has provided almost no information about the underlying molecular mechanisms (Saunders et al 2004). This is in marked contrast to our level of understanding of the circadian clock that regulates daily rhythms, in which studies in various model organisms have led to the discovery of general principles and a detailed understanding of the underlying molecules, which are highly conserved across diverse phyla (Hogenesch and Ueda 2011).…”
mentioning
confidence: 99%
“…Bauer, C. Dziallas, D. Baganz, and G. Staaks, Leibniz Institute of Freshwater Ecology and Inland Fisheries, personal communication). However, studies of the effects of endogenous clocks on ventilation activity and bioirrigation-mediated benthic fluxes, especially in freshwater sediments, are scarce (Saunders et al 2004). Pumping rates are commonly determined under laboratory conditions without …”
mentioning
confidence: 99%